Dermoscopic evaluation of extragenital lichen sclerosus et atrophicus - Sunanda Arun Mahajan; Jayati Shailesh Dave (Mattioli1885, 2022)
Introduction: Lichen sclerosus (LS), is an uncommon inflammatory dermatosis with preferential involvement of anogenital region. Diagnosis of LS is mainly clinical, but clinical differentiation from conditions like vitiligo, morphea may be a difficult task at times that often requires histological analysis. Dermoscopy is one such non-invasive tool which can help diagnose the disease. There is paucity of Indian data on dermoscopy of LS. Objectives: To evaluate clinical, dermatoscopic patterns of LS and correlate them with histopathology. Methods: The study was conducted in a tertiary hospital after obtaining consent from 20 patients. OITEZ e-scope digital microscope was used to evaluate the lesions. Both polarized and nonpolarized mode were used and skin biopsy was done to confirm diagnosis. Results: Based on morphology, LS was classified as scleroatrophic lesions (61.5%), guttate lesions (30.8%) and hyperkeratotic lesions (7.7%). Dermoscopic analysis revealed structureless white to yellow areas  as most common finding (100%) followed by chrysalis like structure (80.8%). Linear irregular vessels were seen in 61.5% lesions and perifollicular scaling in 50.0% lesions. Keratotic plugs were seen in 50.0% lesions. A new characteristic finding, "rosettes" was seen in 38.5% lesions has never been reported with LS before. Non polarized mode was particularly useful for identifying texture changes, keratotic plugs and minute scales which were not visible otherwise.Conclusions: Dermoscopy is a simple diagnostic tool that helps in the early diagnosis of LS with specific pattern which can avoid invasive procedure like biopsy. Both non-polarised and polarized dermoscopy must be done to visualize the changes of LS well.